2008
DOI: 10.1203/pdr.0b013e31816a743e
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering in Cleft Palate and Other Congenital Malformations

Abstract: ABSTRACT:Contributions from multidisciplinary investigations have focused attention on the potential of tissue engineering to yield novel therapeutics. Congenital malformations, including cleft palate, craniosynostosis, and craniofacial skeletal hypoplasias represent excellent targets for the implementation of tissue engineering applications secondary to the technically challenging nature and inherent inadequacies of current reconstructive interventions. Apropos to the search for answers to these clinical conu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 56 publications
(49 reference statements)
0
34
0
4
Order By: Relevance
“…In adult animals, hydrocephaly involves also defects in choroid plexus, but as this is in very early stages in development at the embryonic period we examined, the contribution of CSF overproduction in hydrocephalus causation is hard to assess (Mizusawa, 1997). Sox2 EpINV /+ (H) and Sox2 EpINV/mosaic mutants display developmental defects both in ventricular system/wall formation, as well as in the oral cavity morphology that could contribute to early pathoanatomical events resulting in hydrocephalus and craniofacial defects in humans (Panetta et al, 2008). Thus, disruption of Sox2 function in the embryonic head region could be an additional cause for the development of hydrocephalus later on in life.…”
Section: Discussionmentioning
confidence: 99%
“…In adult animals, hydrocephaly involves also defects in choroid plexus, but as this is in very early stages in development at the embryonic period we examined, the contribution of CSF overproduction in hydrocephalus causation is hard to assess (Mizusawa, 1997). Sox2 EpINV /+ (H) and Sox2 EpINV/mosaic mutants display developmental defects both in ventricular system/wall formation, as well as in the oral cavity morphology that could contribute to early pathoanatomical events resulting in hydrocephalus and craniofacial defects in humans (Panetta et al, 2008). Thus, disruption of Sox2 function in the embryonic head region could be an additional cause for the development of hydrocephalus later on in life.…”
Section: Discussionmentioning
confidence: 99%
“…OCP/Col should be compared with other osteoconductive/osteoinductive materials in this model to assess the bone regenerative properties of OCP/Col. Recently, mesenchymal stem cells (MSC) have been studied for application in regenerative medicine, and the combination of MSC with a scaffold has been investigated for bone regeneration 27,28 . The authors have also previously reported that OCP can be used as an effective scaffold for bone morphogenetic protein-2 (BMP-2) 15 .…”
Section: Discussionmentioning
confidence: 99%
“…There are also allogeneic and synthetic material available for grafting, and while these solve the problem of donor site morbidity, there is still the risk of infection, elicitation of an immune response and problems with structural integrity and contour. 69 The use of tissue engineering could avoid many disadvantages of autogenous grafting, such as donor site morbidity, and could potentially decrease the number of surgeries needed while providing improved outcomes. Only a limited number of studies currently exist exploring palatal tissue engineering, and of these studies, only 36% pertain to human subjects, making it an attractive avenue for future research endeavors ( Table 8).…”
Section: Financial Disclosurementioning
confidence: 99%